2016
DOI: 10.1161/circep.116.004264
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up After Catheter Ablation of Atrioventricular Nodal Reentrant Tachycardia in Children

Abstract: Background-Catheter ablation of the slow conducting pathway (SP) is treatment of choice for atrioventricular nodal reentrant tachycardia (AVNRT). Although there are abundant data on AVNRT ablation in adult patients, little is known about the long-term results ≥3 years after AVNRT ablation in pediatric patients. Methods and Results-Follow-up data from 241 patients aged ≤18 years who had undergone successful AVNRT ablation were analyzed. Median age at ablation had been 12.5 years, and median follow-up was 5.9 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 30 publications
(33 reference statements)
1
15
0
Order By: Relevance
“…Invasive and noninvasive studies revealed sinus tachycardia (4.7%), recurrence of AVNRT (5.2%), and other atrial arrhythmias (6.1%) responsible for recurrent palpitations in a large cohort of 835 adult patients successively ablated for AVNRT. Recurrence of AVNRT has been reported to be higher in younger subjects, up to 11% as reported by Backhoff et al . AVNRT may coexist with other arrhythmias.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…Invasive and noninvasive studies revealed sinus tachycardia (4.7%), recurrence of AVNRT (5.2%), and other atrial arrhythmias (6.1%) responsible for recurrent palpitations in a large cohort of 835 adult patients successively ablated for AVNRT. Recurrence of AVNRT has been reported to be higher in younger subjects, up to 11% as reported by Backhoff et al . AVNRT may coexist with other arrhythmias.…”
mentioning
confidence: 68%
“…The incidence of complete AV block during AVNRT ablation has decreased since the procedure's inception, and is now less than 0.5% . However, late AV block has been documented in the postablation period . Autonomic dysfunction resulting in inappropriate sinus tachycardia has been observed, and Kanjwal et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the reader suggested analysis of the AH interval during AVNRT based on age, as other data in the literature have suggested that the AH interval could be associated with the physical length of the slow pathway . Others have also suggested that the length of the slow pathway is critical to the development of AVNRT, as perhaps there is a critical “length” required for the development of tachycardia, and this length factor may explain why AVNRT is rarer in young children . As suggested by the reader, we compared the AH intervals during AVNRT in children under 10 years of age to those over 10.…”
Section: Intervals With Relation To Agementioning
confidence: 99%
“…20,25,29,30 However, in those aged ≤18 years, recurrence may occur up to 5 years postablation. 31 Success rates are lower (82 %) and the risk of heart block higher (14 %) in patients with complex congenital heart disease. 32 Advanced age is not a contraindication for slow pathway ablation.…”
mentioning
confidence: 99%